(untitled) (Research, Society and Development, 2026)
Esophageal cancer represents one of the greatest challenges in contemporary oncology, being responsible for a high global mortality rate and frequently reported in advanced events. This research aims to synthesize the most recent evidence on esophageal neoplasms, from their anatomical and pathophysiological aspects to contemporary therapeutic approaches. This integrative review analyzed scientific publications from 2015 to 2025, focusing on the anatomical, diagnostic, and therapeutic aspects of esophageal neoplasms. Clinical studies, systematic reviews, and observational research covering topics ranging from molecular biology to clinical practices were included. The results highlight important advances, such as the application of artificial intelligence in endoscopies, the incorporation of minimally invasive techniques, and the introduction of targeted therapies and immunotherapy in the management of advanced cases. Furthermore, a deeper understanding of esophageal anatomy and tumor propagation pathways has influenced the personalization of treatment. However, there are still significant inequalities in access to early diagnosis and modern treatments, especially in low- and middle-income countries. The review highlights the urgent need for public policies, professional training, and integration between science and clinical practice to improve outcomes for patients with this aggressive cancer.